A Scoping Review of Skin Whitening Products: Users’ Knowledge and Motivations, Marketing Strategies, and Adverse Health Effects - Njoku, Anuli; Sawadogo, Wendemi; Pierce, Taryn; Albert, Kaleigh; Plummer, Fabian (International Platform of Registered Systematic Review and Meta-analysis Protocols, 2025)
Keywords: Adverse effect; Business; Marketing; Medicine; Pharmacology; dept.pch

Exposure to Endocrine-Disrupting Chemicals and Early Onset of Menarche: A Systematic Review - Njoku, Anuli; Al-Hassan, Mousa; Tohura, Sharaban; Albert, Kaleigh; Pierce, Taryn; Sawadogo, Wendemi (Pollutants, 2025)
There has been a decline in the age at which girls experience menarche worldwide. Research suggests that exposure to endocrine-disrupting chemicals is linked to negative health consequences, including early onset of menarche. This systematic review examined the association between exposure to endocrine-disrupting chemicals (EDCs) and the early onset of menarche. Comprehensive searches of the PubMed, Embase, Web of Science, and Scopus databases were conducted to find relevant studies published from inception to November 2024. Exposure to certain EDCs, such as particulate matter and phthalates, showed significant associations with earlier menarche onset, while exposure to other EDCs (e.g., pyrethroids) was linked to delayed menarche timing. Overall, there were mixed findings in the relationships between various EDC exposures and menarche onset. Few studies investigated how exposure to EDCs and early menarche differed by race and ethnicity. This underscores the need for more studies that examine the relationship between early menarche onset and exposure to endocrine-disrupting substances. Education and policy approaches are also warranted to address this issue.
Keywords: Age of onset; Epidemiology; MEDLINE; Menarche; Risk assessment; Scopus; dept.pch; endocrine-disrupting chemicals; environmental health; menarche; puberty; reproductive health